Pharmacological modulation of bronchial anaphylaxis induced by aerosol challenge in anaesthetized guinea-pigs. - Daffonchio, L. (1987)
Anaphylactic bronchoconstriction provoked by aerosol challenge, and its pharmacological modulation, has been investigated in anaesthetized pump-ventilated guinea-pigs actively sensitized to ovalbumin (OA). Aerosol challenge (OA 0.03-10 mg ml-1) provoked immediate bronchoconstriction, the degree of which, and its rate of development, was directly related to antigen concentration. Concomitant changes in heart rate and systemic arterial blood pressure following aerosol challenge were reduced compared with systemic (OA, 1 mg kg-1 i.v.) challenge. Unlike systemic challenge, aerosol challenge did not cause a concomitant fall in either circulating leukocyte or platelet count. When a submaximal (microshock) aerosol challenge stimulus (OA, 0.3 mg ml-1, 5 s) was employed, bronchoconstriction was markedly reduced by mepyramine (2 mg kg-1 i.v.). The residual component of bronchoconstriction was enhanced by indomethacin (10 mg kg-1 i.v.), an effect which was reversed by either BW755C (30 mg kg-1 i.v.) or FPL55712 (10 mg kg-1 i.v.). When a supramaximal (macroshock) aerosol challenge stimulus (OA, 10 mg ml-1, 5 s) was employed, bronchoconstriction was also markedly reduced by mepyramine. Residual bronchoconstriction was not altered by indomethacin, slowed but not reduced by indomethacin plus BW755C, and substantially reduced by indomethacin plus FPL55712. The successive incremental antagonism of anaphylactic bronchoconstriction by mepyramine and mepyramine plus indomethacin and FPL55712 indicates that the predominant mediators involved are histamine and leukotrienes, respectively. The failure of indomethacin plus BW755C to inhibit the mepyramine-resistant bronchoconstriction provoked by OA macroshock may reflect the increased generation of leukotrienes via a 5-lipoxygenase isoenzyme resistant to inhibition by BW755C.(ABSTRACT TRUNCATED AT 250 WORDS)